IoT-Enabled Multimodel Emotion Detection and Assistive Smartwatch for Special-Needs Children - A. Samrin; S. Saidharshini; S. Shalima; B. Moohambiga (Journal of Technology Informatics and Engineering, 2026)
Children with neurodevelopmental and communication challenges often find it difficult to express emotional discomfort, stress, or urgent needs, which can delay timely support and increase anxiety. To address this issue, this paper presents an IoT-enabled assistive smartwatch designed to support near real-time emotion inference and basic communication for children with special needs. The proposed system integrates physiological sensing, including heart rate variability, galvanic skin response, and skin temperature, with camera-based facial expression analysis using a multimodal data fusion approach. In addition to emotion-aware monitoring, the smartwatch provides a simple icon-based communication interface and a routine reminder module to support daily activities. The framework enables caregiver-side visualization of emotional trends, communication events, and adherence to routines through a cloud-based dashboard. The system is evaluated through a design-level feasibility assessment using simulated experiments and analysis of benchmark datasets. Overall, this work presents a technically feasible and ethically conscious assistive framework that highlights the potential of combining IoT and emotion-aware computing for supportive care applications.